Factors Influencing University Students’ Choosing Halal Cosmetics : An Exploratory Study - Silvy Astari; Engla Sulistya; Mya Yuwanita Suhanda (Journal of Islamic and South East Asian Finance and Accounting, 2024)
Moslems are supposed to use halal products including cosmetics. This paper aims to explore reasons of university students in choosing halal cosmetics. This study involved three Focus Group Discussions (FGDs) undertaken during May 2024. Each group consisted of seven to ten students who used cosmetic on a daily basis. The result of this study indicated that students were very concern with halal cosmetics. Four points had been highlighted by research participants during the FGDs as factors that they would consider when choosing cosmetics. The four factors have included (i) have the products certified as ‘halal’ by the body that owns authority to do so (ii) do the products have the National Agency of Drug and Food Control logo (i.e. BPOM) (iii) is the price affordable and (iv) is the product suitable with their skin. Research participants acknowledged that they are willing to have extra effort in getting halal cosmetics and will continue to use the halal cosmetics in the future.